Discursive Practices and the Digital Divide. (27th January 2023) - Ivy, Jessica; Mohr-Schroeder, Margaret; Roberts, Thomas; Bush, Sarah B.; Jackson, Christa; Burton, Megan; Edelen, Daniel; Maiorca, Cathrine
Abstract: This team of authors collaborated to transform a middle school–focused informal STEM learning experience to a virtual platform that engaged students in authentic STEM learning experiences while simultaneously promoting discourse.